Contribution of V.H. Hrineveckoho to forming of science bases about traction of trains - Kostenko, A. I. (History of science and technology, 2013)
The questions of history of development of science are illuminated about traction of trains, in particular about planning of combustion engines in 1902-1922 is discussed in the paper. The question of creation of diesel engine and his important value for Russia is analysed in the paper. The contribution of В. Hrineveckiy towards development of steam-engines is shown.